2014
DOI: 10.1111/1365-2745.12345
|View full text |Cite
|
Sign up to set email alerts
|

Novel interactions between non‐native mammals and fungi facilitate establishment of invasive pines

Abstract: Summary1. The role of novel ecological interactions between mammals, fungi and plants in invaded ecosystems remains unresolved, but may play a key role in the widespread successful invasion of pines and their ectomycorrhizal fungal associates, even where mammal faunas originate from different continents to trees and fungi as in New Zealand. 2. We examine the role of novel mammal associations in dispersal of ectomycorrhizal fungal inoculum of North American pines (Pinus contorta, Pseudotsuga menziesii), and nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 55 publications
2
61
0
1
Order By: Relevance
“…There is also experimental evidence of a similar three‐way interaction in New Zealand, where non‐native Australian possums disperse non‐native European and North American suilloid fungi (species of Rhizopogon and Suillus ), facilitating North American pine establishment (Wood et al ., ). Native EMF can also be consumed by non‐native invasive mammals, but current evidence shows that they are not capable of readily colonizing either native or invasive tree species (Wood et al ., ). Interestingly, studies from South America show that native mammals (rodents and a native dwarf deer Pudu pudu ) do not play a significant role in dispersing non‐native fungi because of the scarce abundance of these animals (Nuñez et al ., ).…”
Section: What Factors Can Explain the Success Of Suilloid Fungi?mentioning
confidence: 97%
“…There is also experimental evidence of a similar three‐way interaction in New Zealand, where non‐native Australian possums disperse non‐native European and North American suilloid fungi (species of Rhizopogon and Suillus ), facilitating North American pine establishment (Wood et al ., ). Native EMF can also be consumed by non‐native invasive mammals, but current evidence shows that they are not capable of readily colonizing either native or invasive tree species (Wood et al ., ). Interestingly, studies from South America show that native mammals (rodents and a native dwarf deer Pudu pudu ) do not play a significant role in dispersing non‐native fungi because of the scarce abundance of these animals (Nuñez et al ., ).…”
Section: What Factors Can Explain the Success Of Suilloid Fungi?mentioning
confidence: 97%
“…Successful establishment and invasion of woody plants may be particularly sensitive to belowground symbiont availability, because many of these woody plant species depend on mutualistic microbes like mycorrhizal fungi and nitrogen-fixing bacteria (Nun˜ez and Dickie 2014). In fact, recent research has revealed that both co-invasion of nonnative mutualist species and novel associations with native species determine invasion success (Pringle et al 2009, Dickie et al 2010, Nun˜ez and Dickie 2014, Wood et al 2015. For example, ectomycorrhizal pines appear to invade only when co-invading exotic or cosmopolitan fungi are available (Nun˜ez et al 2009, Dickie et al 2010, Hynson et al 2013, Hayward et al 2015, though introduced trees may form novel associations with native fungi as adults (Parlade´et al 1995, Jairus et al 2011, Trocha et al 2012, Bahram et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…For example, invasive woody plants may be dependent on co-invasion by invasion of their mutualists such as nitrogen fixing bacteria or ectomycorrhizal fungi (Nuñez and Dickie 2014;Traveset and Richardson 2014). Recent studies have also shown that invasive mammals can in turn facilitate the dispersal of invasive ectomycorrhizal fungal species required for the successful establishment of invasive tree species, in both Argentina (Nuñez et al 2013) and New Zealand (Wood et al 2015). Such studies provide evidence the effect of invasive organisms on ecosystem properties can be dependent on, or exacerbated by, co-invasion by other organisms, although this has been explicitly addressed in few studies.…”
Section: Role Of Determinants Of Invasion: Context and Coinvasionmentioning
confidence: 99%